2022
DOI: 10.1039/d1tc05746d
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Q-switched and mode-locked pulses based on PbS/CdS saturable absorbers in an Er-doped fiber laser

Abstract: PbS/CdS quantum dots (QDs) have attracted much attention in the applications of photonic devices owing to their excellent saturable absorption properties. Here, highly monodisperse and perfect crystalline PbS/CdS QDs with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In NIR, PbS CQDs exhibit saturable absorption, which can be exploited as a Q-switcher or passive mode-locker for NIR lasers. 38,39 The ionic precursor of PbS quantum dots may be evenly disseminated using the broad doping concentration adjusted across a wide gradient in the sol−gel process, which is an unmatched benefit of this approach compared to that of the conventional melting method.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NIR, PbS CQDs exhibit saturable absorption, which can be exploited as a Q-switcher or passive mode-locker for NIR lasers. 38,39 The ionic precursor of PbS quantum dots may be evenly disseminated using the broad doping concentration adjusted across a wide gradient in the sol−gel process, which is an unmatched benefit of this approach compared to that of the conventional melting method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous research has shown that aluminum lactate, which is a precursor to alumina, can be used to make alumina-containing glass in a silicon-containing/silicon-free environment. Additionally, by altering the pH of the sol solution, uniform and clear xerogels may be obtained using the chelated lactic acid ligand. , Lead sulfide (PbS) colloidal quantum dots (CQDs) with a wide exciton Bohr radius and a small bandgap show the advantage of producing light at wavelengths ranging from visible to mid-infrared. Moreover, PbS CQDs provide variant nonlinear optical (NLO) responses. In NIR, PbS CQDs exhibit saturable absorption, which can be exploited as a Q-switcher or passive mode-locker for NIR lasers. , The ionic precursor of PbS quantum dots may be evenly disseminated using the broad doping concentration adjusted across a wide gradient in the sol–gel process, which is an unmatched benefit of this approach compared to that of the conventional melting method.…”
Section: Introductionmentioning
confidence: 99%
“…Since Q-switching yields a larger pulse energy while mode-locking produces narrower pulse width, applications can utilize the advantage of both with just a simple adjustment. Some researchers have reported Q-switched and mode-locked lasing, but this is often when using a combination of both passive SA and an intracavity polarization device to switch between the regimes [ 5 , 6 , 7 , 8 , 9 ]. Another Q-switched and mode-locked erbium-doped fiber laser has been reported using gadolinium oxide-based passive SA, although it requires cavity length adjustment in order to obtain stable phase-locked lasing [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another Q-switched and mode-locked erbium-doped fiber laser has been reported using gadolinium oxide-based passive SA, although it requires cavity length adjustment in order to obtain stable phase-locked lasing [ 10 ]. Some SAs have also been reported to produce both Q-switched and mode-locked lasers using this method, but with significantly reduced frequency [ 7 , 11 , 12 , 13 ]. This work, interestingly, will report on the sole use of a passive SA inside a simpler cavity device, with no involvement of any polarization controller or cavity adjustment to produce a Q-switched and mode-locked laser simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…One is introducing the nonlinear polarization evolution (NPE) effect to the fiber laser by using a polarization-dependent component, such as a polarizer [5], tapered fiber [6][7][8], or D-shaped fiber [9]. The other is dispersion management with significantly increased cavity length [10][11][12][13][14][15][16][17][18][19][20]; however, the repetition frequency of the laser is greatly reduced. In addition to the dispersion and nonlinearity, the parameters of the SA can also affect the performance of the QS and ML laser.…”
Section: Introductionmentioning
confidence: 99%